Penerapan Standar Pelayanan Publik Melalui Aplikasi SIPRAJA (Sistem Pelayanan Rakyat Sidoarjo) Di Kantor Kelurahan Celep - Gading Gamaputra; Nur Aini Rosalia; Khoirunisa Khoirunisa; Rd. Kusyeni (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
The Sidoarjo Regency Government innovates to create an online-based Sidoarjo People's Service System (SIPRAJA) to facilitate the correspondence administration process. This study aims to determine the implementation of SIPRAJA services related to the management of type A letters consisting of Birth Certificates, Death Certificates, Inability Certificates, Resident Biodata Certificates, General Village Certificates, and Business Domicile Certificates whose verification process is carried out only at the kelurahan level. This study uses a qualitative descriptive method and data collection techniques through interviews, observation and documentation. The focus of the research is Public Service Standards based on KEPMENPAN No: 63/KEP/M.PAN/2003, namely (1) Standardized Service Procedures for service providers and recipients including complaints (2) Completion Time (3) Service Fees (4) Service Products received in accordance with the provisions (5) Adequate facilities and infrastructure (6) The competence of service officers must comply with the specified criteria. The results showed that the service procedure had been carried out well but was still not well publicized and there was no SIPRAJA SOP board at the Kelurahan Office, the time for the completion of the letter was in accordance with the SOP, the service was free of charge, the results of the letter were in accordance with the provisions, the village infrastructure was adequate, and SIPRAJA operator competence that is in accordance with the provisions.